Efficacy of acute caffeine ingestion for short-term high-intensity exercise performance: a systematic review - Astorino, T. A.; Roberson, D. W. (The Journal of Strength and Conditioning Research, 2010)
Caffeine is the most widely used drug in the world, commonly ingested in coffee, tea, soda, and energy drinks. Its ability to enhance muscular work has been apparent since the early 1900s. Caffeine typically increases endurance performance; however, efficacy of caffeine ingestion for short-term high-intensity exercise is equivocal, which may be explained by discrepancies in exercise protocols, dosing, and subjects' training status and habitual caffeine intake found across studies. The primary aim of this review is to critically examine studies that have tested caffeine's ability to augment performance during exercise dependent on nonoxidative metabolism such as sprinting, team sports, and resistance training. A review of the literature revealed 29 studies that measured alterations in short-term performance after caffeine ingestion. Each study was critically analyzed using the Physiotherapy Evidence Database (PEDro) scale. The mean PEDro score was 7.76 +/- 0.87. Eleven of 17 studies revealed significant improvements in team sports exercise and power-based sports with caffeine ingestion, yet these effects were more common in elite athletes who do not regularly ingest caffeine. Six of 11 studies revealed significant benefits of caffeine for resistance training. Some studies show decreased performance with caffeine ingestion when repeated bouts are completed. The exact mechanism explaining the ergogenic effect of caffeine for short-term exercise is unknown.